The Feudal Origins of Manorial Prosperity in 11th-century England - Vincent Delabastita; Sebastiaan Maes (European Historical Economics Society (EHES), 2020)
Does the prosperity of medieval manors depend on their position in the feudal system? How large are these effects? And what are the economic mechanisms behind it? To answer these questions, we estimate an econometric interactions model on data derived from the Domesday Book, a unique country-wide survey conducted by William the Conqueror two decades after the Battle of Hastings. Domesday Book presents researchers with a unique insight into the feudal structure of a medieval society and the functioning of manorial economies. Using this source, we reinterpret the 11th-century English feudal system as a network in which manors are linked to one another based on their common ownership structure. Our results reveal the existence of external economies of scale: manorial prosperity was closely intertwined with the fortune of their feudal peers, even after including rich agricultural and geographic controls. We decompose these significant, positive interaction effects into two mechanisms: scale and productivity spill-overs. The latter are interpreted as common management structures and knowledge transfers in an information-constrained feudal world.
Keywords: L14; N33; O33; 330; Domesday Book; medieval economic history; network economics